Ad Hoc Networks - Hamilton Ortiz, Jesus; Pachon de la Cruz, Alvaro (IntechOpen, 2017)
A mobile ad hoc network (MANET) is a collection of two or more wireless devices with the capability to communicate with each other without the aid of any centralized administrator. Ad hoc networks have no fixed routers, these nodes can be connected dynamically in an arbitrary manner. MANETs, due to their operational characteristics, the dynamics of their changes and the precariousness of their resources, offer huge challenges due to the architecture and service nature in the next generation of mobile communications. MANETs play an important role in the future of next-generation networks. This special collection identifies and studies the most important concerns in MANETs, and includes contributions from researchers, academics, etc.